Deliberate teaching tools for clinical teaching encounters: A critical scoping review and thematic analysis to establish definitional clarity. (4th March 2019) - Sidhu, Navdeep S.; Edwards, Morgan
Abstract: Purpose and method: We conducted a scoping review of tools designed to add structure to clinical teaching, with a thematic analysis to establish definitional clarity. Results: Six thousand and forty nine citations were screened, 434 reviewed for eligibility, and 230 identified as meeting study inclusion criteria. Eighty-nine names and 51 definitions were identified. Based on a post facto thematic analysis, we propose that these tools be named "deliberate teaching tools" (DTTs) and defined as "frameworks that enable clinicians to have a purposeful and considered approach to teaching encounters by incorporating elements identified with good teaching practice." We identified 46 DTTs in the literature, with 38 (82.6%) originally described for the medical setting. Forty justification articles consisted of 16 feedback surveys, 13 controlled trials, seven pre-post intervention studies with no control group, and four observation studies. Current evidence of efficacy is not entirely conclusive, and many studies contain methodology flaws. Forty-nine clarification articles comprised 12 systematic reviews and 37 narrative reviews. The most number of DTTs described by any review was four. A common design theme was identified in approximately three-quarters of DTTs. Conclusions: Applicability of DTTs to specific alternate settings should be considered in context, and appropriately designed justification studies are warranted to demonstrate efficacy.